Breeding strategies for increasing yield potential in super hybrid rice - Shihua CHENG,Xiaodeng ZHAN,Liyong CAO (Frontiers of Agricultural Science and Engineering, 2015)
Super hybrid rice breeding is a new breeding method combining semi-dwarf breeding and heterosis breeding using germplasm and gene-environment interactions. This paper reviews the breeding strategies of super hybrid rice breeding in China, focusing on the utilization of heterosis of indica and japonica subspecies, construction of ideal plant architecture and pyramiding of disease resistant genes in restorer lines. To develop super hybrid rice, considerable effort should be made to explore genes related with high yield, good quality, resistance to pests and diseases, tolerance to stresses. Molecular breeding methods in combination with crossing techniques should be adopted in super hybrid rice breeding.